UTLEON3: Exploring Fine-Grain Multi-Threading in FPGAs - Daněk, Martin. (Springer New York : Imprint: Springer, 2013)
This book describes a specification, microarchitecture, VHDL implementation and evaluation of a SPARC v8 CPU with fine-grain multi-threading, called micro-threading. The CPU, named UTLEON3, is an alternative platform for exploring CPU multi-threading that is compatible with the industry-standard GRLIB package. The processor microarchitecture was designed to map in an efficient way the data-flow scheme on a classical von Neumann pipelined processing used in common processors, while retaining full binary compatibility with existing legacy programs.  Describes and documents a working SPARC v8, with fine-grain multithreading and fast context switch; Provides VHDL sources for the described processor; Describes a latency-tolerant framework for coupling hardware accelerators to microthreaded processor pipelines; Includes programming by example in the micro-threaded assembly language.    .